Pelayanan optimal barista di Kafe Kalabendana untuk mempererat public relation pelanggan - Jauhari, Ahmad (Maliki Interdisciplinary Journal, 2024)
This study aims to explore key aspects of public service in the coffee industry, with a specific focus on the role of baristas in creating a satisfying experience for customers. The concept of customer satisfaction, as articulated by Kotler & Keller, serves as the foundation for assessing a café’s success, not only in terms of product taste but also in providing a comfortable environment and responding to customer complaints. This research is centered on Kalabendana Coffee in Malang City and will investigate the inhibiting and supporting factors in baristas’ efforts to address customer complaints..